Emerging technologies advancing forage and turf grass genomics - Kopecký, David; Studer, Bruno (Biotechnology advances, 2014)
Grassland is of major importance for agricultural production and provides valuable ecosystem services. Its impact is likely to rise in changing socio-economic and climatic environments. High yielding forage grass species are major components of sustainable grassland production. Understanding the genome structure and function of grassland species provides opportunities to accelerate crop improvement and thus to mitigate the future challenges of increased feed and food demand, scarcity of natural resources such as water and nutrients, and high product qualities. In this review, we will discuss a selection of technological developments that served as main drivers to generate new insights into the structure and function of nuclear genomes. Many of these technologies were originally developed in human or animal science and are now increasingly applied in plant genomics. Our main goal is to highlight the benefits of using these technologies for forage and turf grass genome research, to discuss their potentials and limitations as well as their relevance for future applications.
Keywords: Breeding; Flow cytometry; Next generation sequencing (NGS); Genotyping by sequencing (GBS); lipnicovité; Agriculture; genomika; Genome-wide association studies (GWAS); chov; Epigenetics; Genome zipper; Genome, Plant; Transcriptome sequencing; Cytogenetics; QTL analysis; Biotechnology; biotechnologie; zemědělství; Forage and turf grasses; Poaceae; Genomics; genom rostlinný